2020
DOI: 10.18332/tid/122465
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450 2A6 whole-gene deletion (<i>CYP2A6*4</i> ) polymorphism reduces risk of lung cancer: A meta-analysis

Abstract: INTRODUCTION Lung cancer is the most commonly diagnosed cancer worldwide and is the leading cause of cancer death. Smoking is a major contributor to the pathogenesis of lung cancer. Cytochrome P450 2A6 (CYP2A6) is responsible for the metabolic activation of most tobacco carcinogens. CYP2A6 genetic polymorphism can cause variations in the human metabolism of xenobiotics. We performed this meta-analysis to determine the association between whole-gene CYP2A6 deletion polymorphism (CYP2A6*4) and lung cancer risk.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 40 publications
(60 reference statements)
0
10
0
Order By: Relevance
“…A number of epidemiology studies have confirmed the protective effect of the CYP2A6*4 deletion allele on a smoker's lung cancer risk (27,135,136,146,(148)(149)(150). A meta-analysis of nine case control studies reported a more than 60% reduction in lung cancer incidence among subjects with no functional P450 2A6 (genotype CYP2A6*4/*4 or CYP2A*2/*2) compared to those who carry neither of these alleles (135,136,146,148,(151)(152)(153)(154)(155).…”
Section: Relationship Of Cyp2a6 and Nicotine Metabolism To Lung Cancermentioning
confidence: 98%
See 1 more Smart Citation
“…A number of epidemiology studies have confirmed the protective effect of the CYP2A6*4 deletion allele on a smoker's lung cancer risk (27,135,136,146,(148)(149)(150). A meta-analysis of nine case control studies reported a more than 60% reduction in lung cancer incidence among subjects with no functional P450 2A6 (genotype CYP2A6*4/*4 or CYP2A*2/*2) compared to those who carry neither of these alleles (135,136,146,148,(151)(152)(153)(154)(155).…”
Section: Relationship Of Cyp2a6 and Nicotine Metabolism To Lung Cancermentioning
confidence: 98%
“…A meta-analysis of nine case control studies reported a more than 60% reduction in lung cancer incidence among subjects with no functional P450 2A6 (genotype CYP2A6*4/*4 or CYP2A*2/*2) compared to those who carry neither of these alleles (135,136,146,148,(151)(152)(153)(154)(155). The lung cancer cases in most of these studies included a mixture of smokers and never smokers (typically defined as smoking <100 per lifetime) and, as would be expected, the significance of the protective effect was attenuated if it was not stratified by smoking status (149,150). A few studies have found no relationship between CYP2A6 genotype and lung cancer risk (151,(156)(157)(158).…”
Section: Relationship Of Cyp2a6 and Nicotine Metabolism To Lung Cancermentioning
confidence: 99%
“…As polymorphism of CYP2A6 has wide variants, allele *4 was known as "loss function" enzymes in nicotine metabolism. People with CYP2A6*4 tend to smoke less intensively and having less risk of lung cancer [11], [12]. In this study, we found only two participants showed the expressions of CYP2A6*4 in the case group, and there were no expressions of CYP2A6*4 in the control group, so the risk analysis compares to the wild type of CYP2A6 (CYP2A6*1) could not be performed.…”
Section: Discussionmentioning
confidence: 78%
“…The polymorphism of these enzymes will undermine nicotine metabolism process that has several implications to its own metabolic rate, if polymorphism is presence in the alleles of CYP2A6*4, it could have a protective effect from developing lung cancer due to its nictonine slowly metabolism characteristic [11], [12], [13]. In addition, the CYP2A13 which is highly found in the respiratory epithelium in the upper airway has an inconsistent effect in the development of lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…CYP2A6 exerts a key effect on the outcome of resected gastric cancer [37] and HCC [38] via 5uorouracil metabolism. As the metabolic-activating enzyme of most tobacco carcinogens, CYP2A6 is notably involved with the risk of lung cancer [39] and is a crucial clinical consideration for personalized medicine [40]. The expression levels of CYP2A6 and CYP2A7 are lower in patients with hepatitis B virus and HCV than those in healthy people [41].…”
Section: Discussionmentioning
confidence: 99%